Multi-Functional Core-Shell Nanofibers for Wound Healing - Zhen Li; Shunqi Mei; Yajie Dong; Fenghua She; Puwang Li; Yongzhen Li; Lingxue Kong (Nanomaterials, 2021)
Core-shell nanofibers have great potential for bio-medical applications such as wound healing dressings where multiple drugs and growth factors are expected to be delivered at different healing phases. Compared to monoaxial nanofibers, core-shell nanofibers can control the drug release profile easier, providing sustainable and effective drugs and growth factors for wound healing. However, it is challenging to produce core-shell structured nanofibers with a high production rate at low energy consumption. Co-axial centrifugal spinning is an alternative method to address the above limitations to produce core-shell nanofibers effectively. In this study, a co-axial centrifugal spinning device was designed and assembled to produce core-shell nanofibers for controlling the release rate of ibuprofen and hEGF in inflammation and proliferation phases during the wound healing process. Core-shell structured nanofibers were confirmed by TEM. This work demonstrated that the co-axial centrifugal spinning is a high productivity process that can produce materials with a 3D environment mimicking natural tissue scaffold, and the specific drug can be loaded into different layers to control the drug release rate to improve the drug efficiency and promote wound healing.